Analysis of Halal Tourism Marketing Strategy Through Instagram: A Comparative Study of Indonesia, Malaysia, and Thailand Based on SWOT Analysis - Khamsya Muzamil (i-Tourism: Jurnal Pariwisata Syariah, 2025)
This research examines halal tourism marketing strategies on Instagram through a comparative analysis of Indonesia, Malaysia, and Thailand. The study employs content analysis and SWOT methodology to evaluate posts from official tourism accounts @wonderfulindonesia, @malaysia.truly.asia, and @tourismthailand during the first half of 2024. Findings reveal distinct strategic approaches across the three nations. Indonesia demonstrates strengths in showcasing natural beauty and cultural heritage through visually compelling content, though it shows inconsistency in specifically promoting halal tourism destinations and facilities. Malaysia excels through integrated marketing that effectively highlights its comprehensive halal infrastructure and Muslim-friendly amenities, supported by strong institutional coordination. Thailand successfully positions itself as an inclusive "halal-friendly" destination, skillfully blending halal services within mainstream tourism experiences. The SWOT analysis indicates Malaysia's effective utilization of its strengths through strategic planning, while Indonesia has yet to fully optimize its cultural advantages, and Thailand demonstrates innovative approaches to overcome market limitations. The study concludes that three key factors significantly influence halal tourism marketing effectiveness: robust institutional support, consistent content strategy, and clear market positioning. These findings provide valuable insights for tourism authorities and marketers seeking to enhance their digital marketing approaches in the rapidly growing halal tourism sector, highlighting the importance of tailored strategies that leverage unique national strengths while addressing specific market needs